A Novel Approach on Adaptive Block Steganography Based Crypting Technique for Secure Message Passing - Sahana, Sudipta; Kundu, Abhipsa (International Journal of Computer Sciences and Engineering, 2014)
The enhancement of using internet system has increased the ease of information communication which throws challenge in data security. Now a days harmless and safe data transmission become more vital and significant. Cryptography and Steganography are two important areas of exploration that comprise a great percentage of applications. Cryptography is the expertise technology that involves encoding a message text into an unreadable text form that is known as cipher text and the steganography is an art and technology of hiding information in a multimedia file without causing statistically significant change to this file for involving a secret message transmission. In our suggested work the plain text is converted to a cipher text using the method of Cryptography, where different person can able to use their preferable key for encoding the text and also some Boolean algebraic operations are used in the succeeding steps and after that this cipher text is buried inside a cover media of gray scale image with dimension of 2n x 2n and a secure pictorial block steganography based encryption algorithm is proposed for transferring text message and also revealed the Cryptanalysis and Steganalysis technique for regaining data at receiver side. The experimental outcome indicates that for using different length of text message the distortion of picture is very much less that is negligible in open eyes. At last it can be mentioned that without knowing the appropriate knowledge of cryptanalysis and steganalysis retrieving of message is quite impossible.